FAKTOR YANG MEMPENGARUHI PEMANFAATAN AGEN HAYATI DAN IMPLIKASINYA TERHADAP PENDAPATAN USAHATANI PADI (Oryza sativa L): (Kasus Pada Petani di Kecamatan Rawamerta, Kabupaten Karawang, Provinsi Jawa Barat) - Yana Firmansyah (Fakultas Pertanian Universitas Winaya Mukti, 2025)
YANA FIRMANSYAH.2024. Factors Influencing the Utilization of Biological Agents and Their Implications for Rice Farm Income (Oryza Sativa L). (A Case of a Farmer in Rawamerta District, Karawang Regency, West Java Province). Under Guidance of Euis Dasipah and Tatang Mulyana. This study aims to determine the factors that influence the application of the use of biological agents and their implications for rice farming income. This study used a survey method of farmers who utilize biological agents. The technique of determining respondents was used in the census of 33 farmers. The form of research is verifiative and the analysis techniques used are multiple linear regression and chi square test. The results of the study obtained the demonstration of rice farming using biological agents characterized by an average land exploitation of 1.36 ha. Rice farming activities start from the use of superior and certified seeds; Tillage; Follow-up fertilization; Use of organic fertilizers; Planting seedlings; Weeding; Irrigation; Control of OPT with Biological Agents, Harvesting and post-harvest grain threshing, drying and packaging are carried out conventionally until they are ready for sale. Productivity was achieved before the use of biological agents 6,461 kg/ha and after its 6.9 53 kg/ha. Marketing of production products is carried out at the farmer's place with the selling price received by farmers IDR 6,200 / kg or IDR 6,300 / kg. The use of biological agents by farmers is significantly influenced by: The price of biological agents with negative effects; Land area (positive influence); Experience (positive influence); Attendance in counseling (positive influence for 10% error rate). While factors: The price of organic fertilizer; Cash Capital and Environmental Knowledge of influential farmers are not real. The use of biological agents has implications for increasing rice farming income by Rp 4,011,364 / ha or 19.51%. The increase in income was mainly due to the increase in productivity achievements Keywords: Paddy, Biological Agents, Income.